Postpartum Diet and the Lifestyle of Korean and Chinese Women: A Comparative Study - Li, Jia; Gray, Heewon L.; Kim, Sohyun; Park, Haeryun; Lee, Youngmi; Lee, Hongmie; Song, Kyunghee (Frontiers in Public Health, 2022)
Objective The study investigated and compared postpartum diet and behaviors, nutrition education, and psychological health status among Korean and Chinese postpartum women (0–6 months after delivery). Methods A total of 221 Korean mothers in Gyeonggi-do (South Korea) and 221 mothers in Jinhua (China) participated in the survey between November and December 2018, and the results were statistically analyzed using the SPSS Statistics 25.0 software. Results Many postpartum behaviors, such as postpartum diet pattern and care duration differed between Korean and Chinese mothers. The former showed a stronger desire for nutrition education compared with the latter (p < 0.001). Korean mothers' life and meal satisfaction, and contentment with their husband's support were all ~0.5 points higher compared with Chinese mothers, particularly regarding spousal support (p < 0.001). Postpartum depression stresses positively correlated with postpartum infant care stress and negatively correlated with life satisfaction. In addition, primipara mothers were more in need of infant care support and guidance concerning appropriate baby-feeding techniques compared with multipara mothers. Conclusion Traditional culture was a crucial factor that influenced the perceptions of postpartum women in South Korea and China. Culturally tailored nutrition education and exercise programs may benefit Korean and Chinese women after childbirth.